Improving drought and salinity tolerance in barley by application of salicylic acid and potassium nitrate - Khalaf Ali Fayez; Salih Ali Bazaid (Journal of the Saudi Society of Agricultural Sciences)
Growth and physiological activities of barley (Hordeum vulgare L. cv. Gustoe) grown in soil cultures were evaluated to recognize the ameliorative role of salicylic acid (SA) and KNO3 against the negative effects of salt and water deficit stresses. Barley plants were subjected to three levels of NaCl (50, 100 and 150 mM), three levels of water stress (80%, 70% and 50% of the soil water content (SWC) and the combination of 150 mM NaCl + 50 μM SA, 150 mM NaCl + 10 mM KNO3, 50% SWC + 50 μM SA and 50% SWC + 10 mM KNO3 for two weeks. Salt and water deficit stresses reduced the shoot growth, leaf photosynthetic pigments, K+ contents and provoked oxidative stress in leaves confirmed by considerable changes in soluble carbohydrate, proline, malondialdehyde (MDA), total phenolic compounds, antioxidant activity and Na+ contents. Leaf soluble protein of salt and water deficit treated plants was unaffected. The Na+/K+ ratio increased with increasing salt and water deficit treated plants. Application of 50 μM SA or 10 mM KNO3 to150 mM NaCl and/or 50% SWC treated plants improved these attributes under salt and water stresses. Soluble carbohydrates in stressed plants may have a significant role in osmotic adjustment. It can be concluded that the addition of SA or KNO3 can ameliorate the oxidative stress in barley stressed plants. This ameliorative effect might be maintained through low MDA contents and decreased Na+/K+ ratio in leaves. This study also provided evidence for the ability of barley cultivation in salt and water deficit soils due to its capacity for osmotic adjustment.